.Penerapan BSI Mobile pada Sistem Informasi Manajemen Perbankan Syariah - Ningsih, Nur Ainun; Padli Nasution, M. Irwan (MES Bogor, 2023)
The purpose of this study is to inform customers that m-banking is easy to use, especially in Islamic banking, as they do not have to travel just to transfer money. Since there are still many customers who do not know about m-banking, the number of m-banking users is increasing year by year. With the spread of smartphones, it is getting more attention than Internet banking. The survey method is a qualitative method based on data collection through interviews. From Google Forms. As a result, we realized that many customers did not understand how to use m-banking. This is determined by filling out a Google form. From this we can conclude that Islamic banking information systems will certainly become more sophisticated in this digital age, especially for the large number of Islamic banking customers using m-banking. Keywords: Islamic banking, BSI mobile, information management